2004
DOI: 10.1038/sj.gt.3302294
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant adeno-associated virus-mediated kallikrein gene therapy reduces hypertension and attenuates its cardiovascular injuries

Abstract: Gene therapy of hypertension requires long-term expression of a therapeutic gene to achieve stable reduction of blood pressure. Human tissue kallikrein (HK) cleaves kininogen to produce a potent vasoactive peptide kinin, which plays an important role in the regulation of the cardiovascular and renal functions. In the present study, we have delivered human kallikrein cDNA with an rAAV vector to explore the potential therapeutic effects of kallikrein on hypertension and related secondary complications. A single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 39 publications
3
52
0
Order By: Relevance
“…In order to further investigate the relationship of CYP4A expression level and blood pressure in rats, the present study used recombinant adeno-associated virus (rAAV) as vector to overexpress 4A1 or to block the expression of CYP4A by injection of either rAAV·CYP4A1 or anti4A1, respectively, via the sublingual vein. The rAAV vector system has several unique advantages for gene transfer over other viral vectors (such as plasmid and adenoviral vectors), including a high efficiency of infection, minimal induction of host immune and inflammatory response and driving genes to express in vivo and in vitro in long-term and stably [19,32]. To our surprise, both Northern blots and Western blots demonstrated that after rAAV injection, CYP4A1 was preferentially expressed in the kidney in long-term, with only low level of expression in the liver and poorly in all the other organs.…”
Section: Discussionmentioning
confidence: 99%
“…In order to further investigate the relationship of CYP4A expression level and blood pressure in rats, the present study used recombinant adeno-associated virus (rAAV) as vector to overexpress 4A1 or to block the expression of CYP4A by injection of either rAAV·CYP4A1 or anti4A1, respectively, via the sublingual vein. The rAAV vector system has several unique advantages for gene transfer over other viral vectors (such as plasmid and adenoviral vectors), including a high efficiency of infection, minimal induction of host immune and inflammatory response and driving genes to express in vivo and in vitro in long-term and stably [19,32]. To our surprise, both Northern blots and Western blots demonstrated that after rAAV injection, CYP4A1 was preferentially expressed in the kidney in long-term, with only low level of expression in the liver and poorly in all the other organs.…”
Section: Discussionmentioning
confidence: 99%
“…These epoxygenase cDNAs or GFP were subcloned into the rAAV vector pXXUF 1 downstream of the cytomegalovirus promoter and rAAV-CYP102 F87V, rAAV-CYP2C11-CYPOR, rAAV-CYP2J2, and rAAV-GFP were packed in human 293 cells (American Type Culture Collection, Manassas, VA) and purified by a single-step gravity-flow column purification method as described previously (Xiao et al, 1996;Xiao et al, 1998;Wang et al, 2003b). Purified rAAV viruses were titered using a dot blot method (Wang et al, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…Animal treatment and gene delivery were described previously [6] . Twelve three-month-old male SHRs weighing 250-280 g were randomly divided into two groups (six rats in each group).…”
Section: Animal Treatment and Gene Deliverymentioning
confidence: 99%
“…An 860-bp HK fragment (NotI/NotI) containing an open reading frame was subcloned into pXXUF 1 downstream of CMV to establish the pUF1-HK plasmid. The rAAV·HK and rAAV·LacZ viruses were produced as described previously [6] . The titer of rAAV-HK and rAAV-lacZ was determined by dot blot hybridization.…”
Section: Production and Measurement Of Titers Of Raav Serotype-2 Vectorsmentioning
confidence: 99%
See 1 more Smart Citation